Community dynamics of stabilized dune xerophytic shrubs - Sergio Chozas (Frontiers of Biogeography)
To conciliate the individualistic and holistic paradigms dominating community ecology, I analysed the main factors driving the distribution of xerophytic shrub communities at different scales. I found that the patchy distribution of xerophytic shrubs in southwestern Portugal mainly responds to both local (i.e., soil organic matter) and regional (i.e., climate) factors, confirming the importance of processes acting at different scales. I propose a conceptual model including the ecological dynamics of these communities supported by the analyses of both kinds of drivers and changes in functional diversity. The ecological dynamics between the communities dominated by Stauracanthus genistoides and Ulex australis throughout their co-occurrence area were significantly consistent, despite the factors driving this successional gradient changing regionally. An integrative approach for linking species diversification and distribution assessed the role of edaphic and climatic requirements in the current parapatric distribution of the three species of the genus Stauracanthus.